Climate agreements: Emission quotas versus technology policies - Rolf Golombek; Michael Hoel (University of Oslo, Department of Economics, 2006)
The Kyoto Agreement is the result of international negotiations over many years. However, because of a number of weaknesses, different sorts of climate agreement have been suggested: for example, coordinated R&D activities that reduce abatement costs for all firms. We will compare an agreement focusing only on emissions (a Kyoto type of agreement) with an agreement focusing only on technology, assuming that the costs of abatement are affected by R&D in all firms through technology spillovers. In an emissions agreement, emissions should be restricted to the extent that the carbon price exceeds the Pigovian level. For sufficiently low technology spillovers, an emissions agreement is more efficient than a technology agreement specifying an R&D subsidy to be imposed on all firms in all countries. The opposite may hold if technology spillovers are sufficiently large. Finally, an alternative technology agreement specifying R&D expenditure in each country is more efficient than an agreement specifying an R&D subsidy.
Keywords: H23; O30; Q20; Q28; Q48; 330; climate policy; international climate agreements; R&D policy; technology spillovers; Klimaschutz; Umweltabkommen; Forschungs- und Technologiepolitik; Emissionsrechte; Spillover-Effekt; Theorie